Pengembangan Ekonomi Kreatif Masyarakat melalui Pengolahan Limbah Kulit Kopi Liberika di Desa Jatimulyo: The Development of Economy Creative through Liberica Coffee Waste Processing in Jatimulyo Village - Latief, Madyawati; Heriyanti, Heriyanti; Tarigan, Indra Lasmana; Bemis, Restina; Puspitasari, Ratih Dyah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Coffee pulp is a by-product of coffee cherry processing. It has the potential to be used as a source of antioxidant activity. The dried coffee pulp is commonly referred to as cascara tea, which can be used as a functional drink. The coffee pulp contains caffeine, phenols, and chlorogenic acid that has antioxidant activity. Cascara tea can be fermented into kombucha as a functional drink that contains probiotics. In Jatimulyo Village, coffee cultivation and processing have been developed, but coffee skin waste is not used. Seeing the potential for processing coffee pulp waste into cascara and kombucha cascara tea products can provide added value (value added) to coffee pulp waste. The existence of added value to a product can increase the selling price in the market. The processing of coffee pulp waste into a product that is useful and has a sale value can be used as an effort to develop a creative economy. The results achieved from this activity are increasing the knowledge and skills of Jati Mulyo Village residents in utilizing coffee pulp waste into food products that are useful and have economic selling value.